2010
DOI: 10.4314/eamj.v86i7.54151
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of genital herpes infection among antenatal clinic attendees in South-Eastern Nigeria

Abstract: Background: Herpes simplex virus (HSV) is a major cause of genital ulcer disease worldwide and a significant factor for increased risk of acquisition and transmission of the Human Immune Deficiency Virus (HIV). The determination of the level of knowledge of genital herpes is necessary for the design and implementation of its specific preventive strategies as well as the reduction of the contribution of genital herpes to HIV transmission. Objective: To determine antenatal women's knowledge on genital herpes inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
(7 reference statements)
1
7
0
1
Order By: Relevance
“…For instance, only 41.4% of participants correctly identified that genital herpes is not caused by the same virus as HIV. This finding aligns with previous studies that have reported a lack of awareness about the distinct viral causes of these two diseases [ 10 , 11 ]. This knowledge gap underscores the importance of targeted education campaigns to clarify misconceptions and improve understanding regarding the different aetiologies of STDs.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, only 41.4% of participants correctly identified that genital herpes is not caused by the same virus as HIV. This finding aligns with previous studies that have reported a lack of awareness about the distinct viral causes of these two diseases [ 10 , 11 ]. This knowledge gap underscores the importance of targeted education campaigns to clarify misconceptions and improve understanding regarding the different aetiologies of STDs.…”
Section: Discussionsupporting
confidence: 93%
“…In recent studies, although Nigerian women have been found to have heard about breast cancer, the knowledge related to screening methods such as mammograms was lacking (George et al 2019 ), and in studies where screening methods were known by the respondents, the utilisation of screening methods such as breast self-examination (BSE) and mammography was minimal (Hanson, Abd El-Kader & Ilesanmi 2019 ; Ohaeri & Aderigbigbe 2019 ). Similarly, among diverse categories of women (low, middle and high socio-economic classes), understanding of risk factors and early warning signals of breast cancer was below average (Onwere et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Late diagnosis of breast cancer has been shown to impact differently on survival between affluent groups and those from the socio-economically deprived background (Jemal et al, 2009). Awareness and breast cancer screening practices are poor in developing countries, and this necessitates the need for a proper awareness programme (Onwere et al, 2009).…”
Section: Introductionmentioning
confidence: 99%